High Quantum Efficiency of Stable Sb‐Based Perovskite‐Like Halides toward White Light Emission and Flexible X‐Ray Imaging. Issue 23 (8th September 2022) - Mo, Qionghua; Qian, Qingkai; Shi, Yingrui; Cai, Wensi; Zhao, Shuangyi; Zang, Zhigang
Abstract: Although low‐dimensional hybrid metal halides have emerged as promising light emitters due to their broadband emission originated from self‐trapped exciton (STE), the synthesis of lead‐free halides with high photoluminescence quantum yield remains a challenge. Herein, a series of new luminescent single crystals of antimony‐based metal halides [Na(DMSO)2 ]3 SbBr6− x Cl x ( x  = 0, 2, 3, 4, 6) is synthesized. By optimizing the ratio of Br and Cl, [Na(DMSO)2 ]3 SbBr3 Cl3 exhibits an ultra‐broadband yellow light emission peaking at 606 nm with a full width at half‐maximum of 160 nm and a high photoluminescence quantum yield of 90.6%. Both experimental characterizations and theoretical calculations indicate that STE emission is responsible for the ultra‐broadband yellow light emission. Furthermore, blue LED chip‐pumped white light‐emitting diodes by using the yellow‐emitting [Na(DMSO)2 ]3 SbBr3 Cl3 are demonstrated, showing a correlated color temperature of 3948 K and a color rendering index of 85. Finally, a large‐size and flexible [Na(DMSO)2 ]3 SbBr3 Cl3 scintillator used for X‐ray imaging is prepared by a template assembled method, exhibiting a high spatial resolution of 15.5 lp mm − 1 and a low detection limit of 285.8 nGyair s −1 . This work highlights the potential of Sb‐based halides in solid‐state illumination and X‐ray imaging. Abstract : A series of new air‐stable lead‐free [Na(DMSO)2 ]3 SbBr6− x Cl x ( x  = 0, 2, 3, 4, 6) crystals exhibit broadband yellow emission and high photoluminescence quantum yield. The excellent optical performance of the fabricated crystals facilitates the applications of white light emission and flexible X‐ray imaging.